Pemberdayaan Ekonomi Kelompok Perempuan Nelayan Desa Pabean Kecamatan Dringu Dengan Pelatihan Handicraft - Diana Aqidatun Nisa; Heidy Arviani; Rima Karmelia Fernanda; Ardhelia Damayanti Wirawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The economy in Indonesia has developed after being hit by the Covid-19 pandemic. All levels of society participate in improving the economy, including coastal communities. To improve their economy, fishing families work by fishing at sea and this activity is dominated by men. During the sailing period, an area will be dominated by wives and children. The wives will have two roles while their husbands are away sailing, as housewives and as the financial drivers of the family. This condition requires fisherwomen to play a role as drivers of the family economy. One way that can be done is by empowering fisherwomen. The community service team of the Veteran National Development University of East Java empowered fisherwomen in Pabean Village, Dringu District, Probolinggo Regency by conducting training in making handicrafts with copper wire into brooches with high selling value together with the owner of 'Tenocraft'. The method used in this training is the andragogy learning system. Participants were enthusiastic and able to follow the guidance of the speakers.